Potassium fertigation and organic fertilisation in Syrah grape in Northeastern Brazil: yield, must characteristics and phenolic compounds. - SILVA, A. O. da (2024)
The effect of both potassium and organic fertilisation on grape yield and must composition originating from wine grapevines cultivated in the São Francisco river basin, in the semi-arid region of Northeastern Brazil, is not well known. Since soils from that region usually have low organic matter content, we hypothesise that soil application of organic fertiliser and potassium application through drip irrigation enhances the availability of this nutrient in the soil, and it influences grape yield and quality. Hence, five doses of potassium (0, 20, 40, 80 and 160 kg ha-1) applied through a drip irrigation system and two doses of goat manure as organic fertiliser applied into the soil (0 and 7.5 m3 ha-1) after pruning were evaluated concerning yield and berry quality of grapevine ‘Syrah’ over four growing seasons (April 2013 to July 2015) in Petrolina, state of Pernambuco, Brazil. The experimental design was randomised blocks with 5 replications. We evaluated yield (t ha-1), weight of 100 berries (g), must volume (mL), total soluble solids (°Brix), pH and total titratable acidity (‰), K, Mg and Ca contents and phenolic compounds (total polyphenols, anthocyanins and flavonoids). The increasing application of potassium at the different doses of organic fertiliser did not alter the crop yield, except in the second season. Nonetheless, K concentration in grape must was influenced in the four growing seasons, with higher values at fitted K2O doses by polynomial regression of 83.62 kg ha-1 (first season), 101.25 kg ha-1 (second season), 120.00 kg ha-1 (third season) and 77.99 kg ha-1 (0 m3 ha-1 organic fertiliser) and 96.07 kg ha-1 (7.5 m3 ha-1 organic fertiliser) in the fourth season. The addition of increasing doses of potassium interfered with the wine grape quality, which is an important factor to be considered in relation to its acidity. Organic fertilisation did not affect the most quality characteristics of the grapes.